Taxonomic review of the genus Spulerina Vári 1961 (Lepidoptera: Gracillariidae) in Korea. (3rd April 2023) - Kim, Da-Som; Oh, Jae-in; Byun, Bong-Kyu
ABSTRACT: This study is aimed to review the genus Spulerina Vári, (1961) of the family Gracillariidae from Korea, in which seven species are known. Among them, one species, Spulerina coreana sp. nov ., is described as new to science. Also, two species, S. parthenocissi Kumata & Kuroko, 1988, and S. virgulata Kumata & Kuroko, 1988, are reported for the first time from Korea. All available information for the species including their bibliographies, known host plants, and distributional data are provided. Adults and genitalia of all presented species are briefly redescribed and illustrated.